Porous amorphous silicon, method for manufacturing porous amorphous silicon, and secondary battery

By quenching the eutectic alloy and selectively dissolving the metal, porous amorphous silicon with excellent mechanical characteristics is produced, which solves the problems of long manufacturing time and high manufacturing cost of amorphous silicon thin films, and improves the performance and production economy of lithium-ion batteries.

CN112004777BActive Publication Date: 2025-03-07TOHOKU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980017973.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2019-09-13
Publication Date
2025-03-07
Estimated Expiration
2039-09-13

AI Technical Summary

Technical Problem

In the prior art, the amorphous silicon thin film has a long manufacturing time, is difficult to produce in large quantities, and has a high manufacturing cost, resulting in a reduced charge and discharge efficiency and insufficient battery capacity.

Method used

By cooling the melt containing metal and silicon at a cooling rate of 106 K/sec or more, forming an eutectic alloy, and selectively dissolution of the metal by using an acid or a base, porous amorphous silicon having a sheet-layer structure or a columnar structure is produced.

Benefits of technology

It realizes the manufacture of high-performance porous amorphous silicon at a lower cost and in a short time, improves the charging and discharging efficiency and battery capacity of lithium-ion batteries, and prevents the micronization of the negative electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112004777B_ABST
    Figure CN112004777B_ABST
Patent Text Reader

Abstract

The present invention provides a porous amorphous silicon which can improve battery performance such as charge and discharge efficiency and battery capacity when used as a negative electrode material, a method for manufacturing porous amorphous silicon which can manufacture porous amorphous silicon composed entirely of amorphous silicon at a relatively low cost and in a short time, and a secondary battery using the porous amorphous silicon as a negative electrode material. 6 The melt containing metal and silicon is cooled at a cooling rate of more than 10000 K / s to form a eutectic alloy composed of the metal and silicon, and the metal is selectively dissolved from the eutectic alloy using an acid or an alkali, thereby obtaining porous amorphous silicon. The porous amorphous silicon has a lamellar structure or a columnar structure with an average particle size or an average column diameter of 1 nm to 100 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to porous amorphous silicon, a method for manufacturing porous amorphous silicon and a secondary battery. Background Art

[0002] In order to realize a sustainable and environmentally friendly society, the use of renewable energy is important. However, in fiscal 2016, renewable energy accounted for only 14.5% of Japan's electricity sources. The reason is that the amount of electricity generated from solar and wind power is affected by the season and climate, so the balance between demand and supply is easily broken, and it cannot become a stable source of electricity. In order to make renewable energy a stable and main source of electricity, the development of storage technology is the most important technical issue. It is no exaggeration to say that the high performance and low cost of storage batteries for this purpose are the key to the success or failure of renewable energy in the future.

[0003] Lithium-ion batteries using liquid electrolytes that have been put into practical use (liquid lithium-ion batteries) had a global market size of approximately 1.1 trillion yen in 2016, and are still growing steadily due to the social push to achieve a low-carbon society. Compared with liquid lithium-ion batteries, lithium-ion batteries using solid electrolytes (all-solid-state lithium-ion batteries) have very high electrochemical stability of solid electrolytes, are suitable for high-potential electrode active materials, and can seek high energy density of batteries. In addition, since they have both flame retardancy and high temperature resistance, if they are batteries for electric vehicles, the safety components of the battery pack can be greatly reduced, and low costs can be expected. On the other hand, all-solid-state lithium-ion batteries are under development, and it is necessary to develop electrolyte materials with high ionic conductivity, reduce the interface resistance between electrode active materials and electrolytes, and develop high-performance positive and negative electrode materials.

[0004] Liquid lithium-ion batteries and all-solid-state lithium-ion batteries use carbon active materials as negative electrode materials, and their weight capacity density is about 370 mAh / g. On the other hand, if silicon is used as the negative electrode material, the theoretical weight capacity density increases to about 4200 mAh / g (for example, refer to non-patent document 1), so the capacity can be expected to increase by about 11 times. In addition, due to the Li / Li + With an operating potential as low as 0.5V and abundant Si elements naturally present, if silicon is used as the negative electrode material of lithium-ion batteries, the driving range of electric vehicles can be greatly extended, allowing smartphones to be used for a long time.

[0005] However, due to the reaction of lithium embedding during charging, the silicon electrode in the lithium-ion battery alloys from Si+4.4Li to Li4.4Si, and expands to about 4 times in volume. Due to this expansion, the electrode breaks, and after about 10 cycles of charge and discharge, the battery capacity is reduced to less than half. Therefore, compared with the previous negative electrode materials composed of carbon-based active materials, although the silicon electrode has a high weight capacity density, it has a technical problem of extremely short life due to micronization caused by volume change.

[0006] Therefore, in order to solve the technical problem of electrode cracking, a technology has been proposed that uses thin films or particles of amorphous silicon, which are not easily damaged even during alloying with Li insertion and have excellent mechanical properties, as negative electrode materials (for example, refer to Non-Patent Documents 2 and 3).

[0007] Regarding the formation of amorphous silicon, the following theory based on thermodynamic considerations has been proposed: if the liquid is supercooled to a temperature of 243K or more below the melting point, since the free energy of amorphous silicon is lower than the free energy of liquid silicon, the supercooled silicon to above 243K may spontaneously form into amorphous silicon (for example, refer to non-patent document 4).

[0008] In addition, in order to more effectively prevent the electrode from cracking, it is considered to form an amorphous silicon electrode with porous particles. That is, since a plurality of voids are formed inside the porous particles, if the amorphous silicon electrode is formed with porous particles, when the volume expands due to alloying with Li, the volume of the voids becomes a gap, so that the electrode can be more effectively prevented from being pulverized.

[0009] Conventionally, there is a method for producing porous particles containing amorphous silicon by heating the particles at 100 K / sec to 1×10 5 K / sec to rapidly cool an alloy melt containing at least one element M selected from the group consisting of Sn, Al, Pb, In, Ni, Co, Ag, Mn, Cu, Ge, Cr, Ti, and Fe and Si to form a rapidly cooled alloy, and removing the element M contained in the rapidly cooled alloy by dissolving it with an acid or alkali that can dissolve the element M, thereby obtaining an aggregate of porous particles composed of Si and a portion of which is an amorphous phase (for example, refer to patent document 1); or a method of using a solvothermal method to react silicon tetrachloride (SiCl4) with Mg to form Si and MgCl2, further heat treating and rapidly cooling it, and then desorbing MgCl2 to produce amorphous silicon having a porous structure (for example, refer to non-patent document 5).

[0010] In addition, during the solidification of the alloy, it usually forms a dendrite in which primary dendrites grow while secondary dendrites grow in a direction perpendicular to them. If the cooling rate of solidification is increased, the dendrites as a whole become smaller, and at the same time, the generation of primary dendrite arms is suppressed, and the spacing between secondary dendrites becomes smaller. If the dendrite arm spacing (DAS) becomes smaller, the eutectic or compound distributed in the gap between them also becomes smaller, and an overall fine structure can be obtained. DAS (μm) is particularly dependent on the cooling rate V (K / sec) and follows the relationship of formula (1).

[0011] DAS=aV -n (1)

[0012] Here, a is a constant determined by the alloy and is usually 10 to 100, and n is independent of the alloy and is approximately 0.3.

[0013] In addition, the inventors of the present application have developed a device and method for producing single-micrometal powders based on a gas atomization method, which can stably mass-produce spherical metal powders with small particle size, high purity and high melting point (for example, refer to Patent Document 2).

[0014] Prior art literature

[0015] Non-patent literature

[0016] Non-patent document 1: U. Kasavajjula et al., "Nano- and bulk-silicon-based insertion anodes for lithium-ion secondary cells", Journal of Power Sources, 2007, 163, p. 1003

[0017] Non-patent document 2: JW Lang et al., "Two-Phase Electrochemical Lithiation in Amorphous Silicon", Nano Letters, 2013, 13, p. 709

[0018] Non-patent document 3: Magasinski et al., “High-performance lithium-ion anodes using a hierarchical bottom-up approach”, Nature Materials, 2010, 9, p. 353 Non-patent document 4: Shao et al., “An Analysis of the Formation of Bulk Amorphous Silicon from the Melt”, Metallurgical and Materials Transactions A, 1998, 29A, p. 1825

[0019] Non-patent document 5: Liangdong Lin et al., "Mesoporous Amorphous Silicon: ASimple Synthesis of a High-Rate and Long-Life Anode Material for Lithium-IonBatteries", Angew.Chem.Int.Ed., 2016, 55, p.14063-14066

[0020] Patent Literature

[0021] Non-patent document 1: Japanese Patent No. 3827642

[0022] Non-patent document 2: Japanese Patent Application Publication No. 2019-14917 Summary of the invention

[0023] Technical Problems to be Solved by the Invention

[0024] In non-patent document 2, although amorphous silicon thin film with mechanical properties superior to crystalline silicon is used as the negative electrode material, it takes time to manufacture the amorphous silicon thin film, so there is a technical problem that it is difficult to mass produce. For example, although amorphous silicon thin film can be manufactured by laminating by sputtering in an argon atmosphere, the usual film growth rate is 1nm / second, and it takes about 1.5 hours to make an amorphous layer of several microns on a wafer-level area. Therefore, if economic efficiency is considered, when used as a negative electrode material, a negative electrode material in which the amorphous silicon thin film is not fully grown has to be used, and the content of Si that helps the charge and discharge of the battery becomes less, and there will be a technical problem of reduced charge and discharge efficiency.

[0025] In addition, in Non-Patent Document 3, although amorphous silicon particles are produced by a vapor phase growth method using silane gas (SiH4) and used as negative electrode materials, the production of the amorphous silicon particles requires an expensive manufacturing system and control device, and there is a technical problem of high manufacturing cost due to the complex process and high raw material costs. Therefore, the technology of Non-Patent Document 3 has not expanded the economic scale for mass production.

[0026] Furthermore, Non-Patent Document 4 proposes a thermodynamic theory regarding a method for producing amorphous silicon from silicon in a supercooled liquid state, but there is currently no report on the successful production of amorphous silicon by rapid cooling of liquid based on this theory.

[0027] The size of the structure of the porous silicon particles is based on the DAS of formula (1). In the case of a crystalline phase, for example, when a=10, in order to obtain a DAS of less than 100 nm, 10 6 In order to obtain porous particles of amorphous silicon with a finer structure, a higher quenching rate is required. In the method for producing porous particles described in Patent Document 1, since the quenching rate when forming the alloy is 10 5 K / sec, so only a part of it becomes amorphous silicon, and there is a technical problem that porous particles that are entirely amorphous silicon cannot be obtained. In particular, in Al-Si alloys, there is a technical problem that only a single phase of Al and a single phase of Si can be obtained as crystalline phases.

[0028] In addition, the method for manufacturing amorphous silicon described in Non-Patent Document 5 uses a solvent thermal method, which requires an autoclave and other devices and strict temperature and pressure management, resulting in a technical problem of high manufacturing costs. In addition, the method of Non-Patent Document 5 uses a solvent thermal method, so a lamellar structure is not generated.

[0029] The present invention is made with a view to the above-mentioned technical problems, and its purpose is to provide a porous amorphous silicon which can improve battery performance such as charge and discharge efficiency and battery capacity when used as a negative electrode material, a method for manufacturing porous amorphous silicon which can manufacture porous amorphous silicon composed entirely of amorphous silicon at a relatively low cost and in a short time, and a secondary battery using the porous amorphous silicon as a negative electrode material.

[0030] Technical means to solve technical problems

[0031] In order to achieve the above-mentioned purpose, the inventors of the present application have conducted intensive research by effectively utilizing the technology for producing single-particle metal powders based on the gas atomization method described in the independently developed patent document 2, the insights into the rapid cooling and solidification of metal silicon alloys, and the microstructure observation technology using an electron microscope, and as a result, completed the present invention.

[0032] That is, the porous amorphous silicon of the present invention is characterized in that it has a lamellar structure or a columnar structure with an average particle size or an average columnar diameter of 1nm to 100nm. Preferably, the porous amorphous silicon of the present invention has a lamellar structure with a spacing of 1nm to 100nm between adjacent lamellar layers, or a columnar structure with a spacing of 1nm to 100nm between adjacent pillars.

[0033] The method for producing porous amorphous silicon of the present invention is characterized in that: 6 The melt containing the metal and silicon is cooled at a cooling rate of 0.1 K / s or higher to form a eutectic alloy composed of the metal and the silicon, and the metal is selectively dissolved from the eutectic alloy using an acid or an alkali, thereby obtaining porous amorphous silicon.

[0034] The method for producing porous amorphous silicon of the present invention can be suitably used to produce the porous amorphous silicon of the present invention. The method for producing porous amorphous silicon of the present invention comprises: 6 By cooling a melt containing metal and silicon at a cooling rate of more than K / s, the domain size of the silicon phase in the structure of the eutectic alloy can be made into 1nm~100nm. By selectively dissolving the metal from the eutectic alloy, the porous amorphous silicon of the present invention having a lamellar structure or a columnar structure with an average particle size or an average column diameter of 1nm~100nm can be manufactured. In addition, the method for manufacturing porous amorphous silicon of the present invention can also make the domain size of the metal phase in the structure of the eutectic alloy be made into 1nm~100nm. At this time, the porous amorphous silicon of the present invention having a lamellar structure with a spacing of 1nm~100nm between adjacent lamellar layers, or the porous amorphous silicon of the present invention having a columnar structure with a spacing of 1nm~100nm between adjacent pillars can be manufactured.

[0035] The method for producing porous amorphous silicon of the present invention can be carried out by 6 The melt is cooled at a cooling rate of more than 10000 K / s to produce porous amorphous silicon composed entirely of amorphous silicon. In addition, by further increasing the cooling rate, the phase domain size of the silicon phase in the structure of the eutectic alloy can be reduced to 1nm to 50nm, and porous amorphous silicon with an average particle size or average column diameter of 1nm to 50nm can be produced.

[0036] Since the method for manufacturing porous amorphous silicon of the present invention consists of the process of rapidly cooling the melt and dissolving the metal using an acid or an alkali, it is not necessary to use expensive equipment, etc., and porous amorphous silicon can be manufactured at a low cost and in a short time. In addition, by using silicon with the highest Clark value other than oxygen, and further using metals such as aluminum with a high Clark value as raw materials, porous amorphous silicon can be manufactured cheaply. In addition, therefore, it is easy to expand the economic scale for mass production.

[0037] Since the porous amorphous silicon of the present invention is composed of fully grown porous amorphous silicon, when used as a negative electrode material, it is possible to improve battery performance such as charge and discharge efficiency and battery capacity. Preferably, the porous amorphous silicon of the present invention has a double continuous structure. In addition, the porous amorphous silicon of the present invention preferably has a three-dimensional network structure continuous with amorphous silicon and at the same time has continuous voids. In addition, in terms of the ratio of elements other than oxygen, silicon is preferably 90% or more.

[0038] When the porous amorphous silicon of the present invention is used as the negative electrode material of a lithium-ion battery, even if silicon and lithium alloy and expand in volume, the expansion occurs in a manner that fills the gaps in the pores, so there is almost no change in appearance. Furthermore, since amorphous materials have no dislocation defects and grain interfaces, a uniform stress dispersion is formed for mechanical stress loads. Therefore, compared with crystalline materials, the porous amorphous silicon of the present invention can have both high strength and high elasticity, and is not afraid of volume expansion when silicon and lithium alloy. In this way, when the porous amorphous silicon of the present invention is used as the negative electrode material of a lithium-ion battery, the negative electrode material can be prevented from being micronized. In addition, not limited to the negative electrode material of lithium-ion batteries, the porous amorphous silicon of the present invention can also be used as thermoelectric materials, solar cells, electronic device components, filter materials, and optical materials.

[0039] In the method for manufacturing porous amorphous silicon of the present invention, the eutectic alloy can be manufactured by any method as long as it is a method for rapid cooling. For example, it can be a strip or foil with an average thickness of 0.1μm to 1mm manufactured by a single roll liquid quenching method or a double roll liquid quenching method, or it can be a powder with an average particle size of 10nm to 30μm manufactured by a gas atomization method or a water atomization method.

[0040] In the method for manufacturing porous amorphous silicon of the present invention, as long as it is a eutectic alloy containing metal and Si, the eutectic alloy can be any alloy, for example, it can also be an Al-Si alloy. At this time, it is preferably contained in an atomic percentage of 1% to 50% of the Si, thereby making it possible to manufacture porous amorphous silicon with an average porosity of 50% to 99%. In addition, the eutectic alloy may also be a Fe-Si alloy, a Ni-Si alloy, a Cr-Si alloy, an Ag-Si alloy, or a Cu-Si alloy. At this time, it is preferably contained in an atomic percentage of 50% to 90% of the Si, thereby making it possible to manufacture porous amorphous silicon with an average porosity of 10% to 50%. In addition, the porosity here refers to the content of the component selectively dissolved from the eutectic metal in the eutectic metal in an atomic percentage. For example, when all components except silicon are dissolved from the eutectic metal, the void ratio (%) = the atomic percentage content of the components dissolved from the eutectic metal in the eutectic metal (%) = 100 (%) - the atomic percentage content of silicon in the eutectic metal (%).

[0041] In addition, the eutectic alloy can be a binary or multi-element eutectic alloy represented by M1-Si (M1 is one or more elements selected from Al, Ag, As, Au, Be, Ca, Cr, Cu, Mg, Pd, Pt, Y, Co, Fe, Mn, Ti, and Zr), or it can be a ternary or multi-element eutectic alloy represented by M2-Al-Si (M2 is one or more elements selected from Ca, Cu, Ge, P, Mn, Na, Sb, Sn, Sc, Sr, and Ti).

[0042] The secondary battery of the present invention is characterized in that the negative electrode material is composed of the porous amorphous silicon of the present invention.

[0043] The secondary battery of the present invention has high battery capacity and good cycle characteristics because the negative electrode material has a high weight capacity density and is composed of porous amorphous silicon that is not afraid of volume expansion. In addition, the negative electrode material can be prevented from being micronized due to electrode rupture.

[0044] Effects of the Invention

[0045] According to the present invention, there can be provided a porous amorphous silicon which can improve battery performance such as charge and discharge efficiency and battery capacity when used as a negative electrode material, a method for manufacturing porous amorphous silicon which can manufacture porous amorphous silicon composed entirely of amorphous silicon at a relatively low cost and in a short time, and a secondary battery in which the porous amorphous silicon is used as a negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, (a) scanning electron microscope (SEM) photograph of porous amorphous silicon manufactured using an Al-Si alloy with a blending ratio of Si:Al=20:80 (atomic %) and a single-roll liquid quenching method, (b) an SEM photograph with a higher magnification than (a), and (c) an SEM photograph with a higher magnification than (b).

[0047] Figure 2 for Figure 1 (a) Transmission electron microscope (TEM) photograph of porous amorphous silicon, (b) TEM photograph at a higher magnification than (a), and Fourier transform image (inset) are shown.

[0048] Figure 3 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, porous amorphous silicon is manufactured using Al-Si alloy powder with a blending ratio of Si:Al=20:80 (atomic %) and produced by gas atomization using He gas: (a) scanning electron microscope (SEM) photograph, (b) SEM photograph at a higher magnification than (a), (c) SEM photograph at a higher magnification than (b), and (d) SEM photograph of a portion different from (b) at a higher magnification than (a).

[0049] Figure 4 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, porous amorphous silicon is manufactured using Al-Si-Ti alloy powder with a blending ratio of Si:Al:Ti=19.5:79.5:1.0 (atomic %) and produced by atomization using He gas, (a) a scanning electron microscope (SEM) photograph, and (b) a SEM photograph at a higher magnification than (a).

[0050] Figure 5 In (a), Figure 1 The XRD spectrum of porous amorphous silicon shown in (b) is Figure 3 The XRD spectrum of porous amorphous silicon shown in (c) is Figure 4 (a) is an XRD spectrum of porous amorphous silicon, and (d) is an XRD spectrum of crystalline Si nanopowder of a comparative example.

[0051] Figure 6 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, porous amorphous silicon is manufactured using Al-Si alloy powder with a blending ratio of Si:Al=3:97 (atomic %) and produced by gas atomization using He gas: (a) scanning electron microscope (SEM) photograph, (b) SEM photograph with a higher magnification than (a), (c) SEM photograph with a higher magnification than (b), and (d) SEM photograph with a higher magnification than (c).

[0052] Figure 7In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, porous amorphous silicon is manufactured using Al-Si alloy powder with a blending ratio of Si:Al=12.5:87.5 (atomic %) and produced by atomization using Ar gas: (a) scanning electron microscope (SEM) photograph, (b) SEM photograph at a higher magnification than (a), and (c) SEM photograph at a higher magnification than (b).

[0053] Figure 8 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, (a) scanning electron microscope (SEM) photograph of porous amorphous silicon manufactured using Al-Si alloy powder with a blending ratio of Si:Al=12.5:87.5 (atomic %) and a single-roll liquid quenching method, and (b) an SEM photograph with a higher magnification than (a).

[0054] Fig. 9 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, (a) scanning electron microscope (SEM) photograph of porous amorphous silicon manufactured using Al-Si alloy powder with a blending ratio of Si:Al=30:70 (atomic %) and a single-roll liquid quenching method, and (b) an SEM photograph with a higher magnification than (a).

[0055] Fig.10 In order to utilize the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, (a) scanning electron microscope (SEM) photograph of porous amorphous silicon manufactured using Al-Si alloy powder with a blending ratio of Si:Al=40:60 (atomic %) and a single-roll liquid quenching method, and (b) an SEM photograph with a higher magnification than (a).

[0056] Fig.11 for Figure 8 XRD spectrum of porous amorphous silicon is shown.

[0057] Fig.12 To illustrate (a) the use of Figure 1 (a) is a graph showing the battery cycle characteristics evaluation test results of a lithium ion battery using porous amorphous silicon as a negative electrode material, and (b) is a graph showing the battery cycle characteristics evaluation test results of a lithium ion battery using crystalline Si particles of a comparative example as a negative electrode material. DETAILED DESCRIPTION

[0058] Hereinafter, embodiments of the present invention will be described based on examples and the like.

[0059] The porous amorphous silicon of the embodiment of the present invention has a lamellar structure or a columnar structure with an average particle size or an average columnar diameter of 1nm to 100nm. In addition, the porous amorphous silicon of the embodiment of the present invention has a lamellar structure with a spacing between adjacent lamellar layers of 1nm to 100nm, or a columnar structure with a spacing between adjacent pillars of 1nm to 100nm. The porous amorphous silicon of the embodiment of the present invention is preferably manufactured by the manufacturing method of the porous amorphous silicon of the embodiment of the present invention.

[0060] In the method for producing porous amorphous silicon according to the embodiment of the present invention, first, 6 The melt containing the metal and silicon is cooled at a cooling rate of 1000 K / s or more to form a eutectic alloy composed of the metal and silicon. Then, the metal is selectively dissolved from the eutectic alloy using an acid or an alkali. Thus, porous amorphous silicon can be obtained.

[0061] In the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, the eutectic alloy can be manufactured, for example, by a single-roll liquid quenching method or a double-roll liquid quenching method. At this time, the eutectic alloy manufactured is preferably in the form of a strip or foil with an average thickness of 0.1 μm to 1 mm. In addition, the eutectic alloy can also be manufactured by a gas atomization method or a water atomization method. At this time, the eutectic alloy manufactured is preferably in the form of a powder with an average particle size of 10 nm to 30 μm.

[0062] In addition, in the method for manufacturing porous amorphous silicon according to an embodiment of the present invention, the eutectic alloy may be, for example, an Al-Si alloy. In this case, it is preferred that 1% to 50% Si is contained in atomic percentage, thereby enabling porous amorphous silicon with an average porosity of 50% to 99% to be manufactured. In addition, the eutectic alloy may also be a Fe-Si alloy, a Ni-Si alloy, a Cr-Si alloy, an Ag-Si alloy, or a Cu-Si alloy. In this case, it is preferred that 50% to 90% Si is contained in atomic percentage, thereby enabling porous amorphous silicon with an average porosity of 10% to 50% to be manufactured.

[0063] In addition, the eutectic alloy may be a binary or multinary eutectic alloy represented by M1-Si (M1 is one or more elements selected from Al, Ag, As, Au, Be, Ca, Cr, Cu, Mg, Pd, Pt, Y, Co, Fe, Mn, Ti, and Zr), or a ternary or multinary eutectic alloy represented by M2-Al-Si (M2 is one or more elements selected from Ca, Cu, Ge, P, Mn, Na, Sb, Sn, Sc, Sr, and Ti). In addition, the eutectic alloy may also be an amorphous alloy.

[0064] Next, the operation will be described.

[0065] In the method for producing porous amorphous silicon according to the embodiment of the present invention, when forming the eutectic metal, the 6 The melt containing metal and silicon is cooled at a cooling rate of more than K / s, so that the domain size of the silicon phase in the structure of the eutectic alloy can be made into 1nm~100nm, and the domain size of the metal phase in the structure of the eutectic alloy can be made into 1nm~100nm. By selectively dissolving the metal from the eutectic alloy, it is possible to manufacture porous amorphous silicon according to an embodiment of the present invention having an average particle size or an average columnar diameter of 1nm~100nm, a lamellar structure with an interval of 1nm~100nm between adjacent lamellar layers, or a columnar structure with an interval of 1nm~100nm between adjacent pillars.

[0066] The method for manufacturing porous amorphous silicon according to an embodiment of the present invention comprises: 6 The melt is cooled at a cooling rate of more than 10000 K / s to produce porous amorphous silicon composed entirely of amorphous silicon. In addition, by further increasing the cooling rate, the phase domain size of the silicon phase in the structure of the eutectic alloy can be reduced to 1nm to 50nm, and porous amorphous silicon with an average particle size or average column diameter of 1nm to 50nm can be produced.

[0067] Since the method for manufacturing porous amorphous silicon according to the embodiment of the present invention consists of a process of rapidly cooling a melt and dissolving a metal using an acid or an alkali, it is not necessary to use expensive equipment, etc., and porous amorphous silicon can be manufactured at a low cost and in a short time. In addition, by using silicon having the highest Clark value other than oxygen, and further using metals such as aluminum having a high Clark value as raw materials, porous amorphous silicon can be manufactured inexpensively. In addition, this makes it easy to expand the economic scale for mass production.

[0068] In addition, since the porous amorphous silicon of the embodiment of the present invention manufactured by the manufacturing method of the porous amorphous silicon of the embodiment of the present invention is composed of fully grown porous amorphous silicon, it can improve battery performance such as charge and discharge efficiency and battery capacity when used as a negative electrode material. When the porous amorphous silicon of the embodiment of the present invention is used as a negative electrode material of a lithium-ion battery, even if the volume expands due to the alloying of silicon with lithium, the expansion occurs in a manner that fills the gaps in the pores, so there is almost no change in appearance. In addition, since the porous amorphous silicon of the embodiment of the present invention can have both high strength and high elasticity compared to crystalline materials, it is not afraid of volume expansion when silicon is alloyed with lithium. In this way, when the porous amorphous silicon of the embodiment of the present invention is used as a negative electrode material of a lithium-ion battery, the negative electrode material can be prevented from being pulverized.

[0069] In addition, the porous amorphous silicon of the embodiment of the present invention is not limited to the negative electrode material of the lithium ion battery, and can also be used as a thermoelectric material, a solar cell, an electronic device component, a filter material, and an optical material. In addition, it is preferred that the porous amorphous silicon of the embodiment of the present invention has a double continuous structure. In addition, it is preferred that the porous amorphous silicon of the embodiment of the present invention has a three-dimensional network structure continuous with amorphous silicon and has continuous voids at the same time. In addition, in terms of the ratio of elements other than oxygen, it is preferred that silicon is 90% or more.

[0070] Example 1

[0071] Porous amorphous silicon is manufactured using the method for manufacturing porous amorphous silicon according to an embodiment of the present invention. First, silicon (in block form, with a purity of 99.999% or more) and aluminum are mixed in a ratio of Si:Al=20:80 (atomic %), and arc-melted in a vacuum furnace in a state replaced with argon to form a melt. A strip-shaped Al-Si alloy with a plate thickness of about 15 μm is produced from the melt using a single-roll casting machine and a single-roll liquid quenching method. The Al-Si alloy is a eutectic alloy composed of Al and Si. The Al-Si alloy is immersed in hydrochloric acid at a concentration of 5N and a temperature of 60°C for 24 hours to dissolve Al and manufacture a porous body composed of silicon.

[0072] Figure 1 and Figure 2 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the obtained porous body are shown respectively. Figure 2 The Fourier transform of the TEM image is shown in (b). Figure 1 and Figure 2 As shown, the obtained material forms a porous structure with an average particle size and an average column diameter of about 10nm, especially Figure 1 (c) in the figure was confirmed to have a 10nm-wide lamellar structure. It was also confirmed that the interval between adjacent lamellar layers in the lamellar structure was less than several tens of nm. Figure 2 The Fourier transform diagram of (b) shows a halo pattern, which confirms that the material is amorphous.

[0073] Figure 5 (a) shows the measurement result of the obtained porous body based on the X-ray diffraction (XRD) method. In addition, as a comparative example, Figure 5 (d) in FIG. 1 shows the measurement results of commercially available crystalline Si nanopowder based on the X-ray diffraction (XRD) method. Figure 5 As shown in (a) of FIG. 1 , there is no sharp peak in the XRD spectrum, and a smooth shape is formed, which confirms that the obtained porous body is amorphous rather than crystalline. Based on the above results, it can be said that Figure 1 and Figure 2 The material shown is porous amorphous silicon.

[0074] Example 2

[0075] Next, silicon (in block form, with a purity of 99.9% or more) and aluminum are mixed in a ratio of Si:Al = 20:80 (atomic %), and arc-melted in a vacuum furnace under argon substitution to form a melt at 1400°C. The melt is crushed using a gas atomization device shown in Patent Document 2 using 10MPa helium to produce an Al-Si alloy powder with a particle size of about 10μm or less. The Al-Si alloy powder is a eutectic alloy composed of Al and Si. The Al-Si alloy powder is immersed in hydrochloric acid at a concentration of 5N and a temperature of 60°C for 24 hours to dissolve Al, thereby producing a porous body composed of silicon.

[0076] Figure 3 The scanning electron microscope (SEM) image of the obtained porous body is shown. Figure 3 As shown in FIG. 1 , it was confirmed that the obtained substance formed a porous lamellar structure with an average particle size and an average column diameter of about 20 to 30 nm (reference Figure 3 (b), (c)) and columnar structures with an average column diameter of about 100 nm (reference Figure 3 (d) in the figure). It was also confirmed that the spacing between adjacent sheets in the sheet structure is less than tens of nanometers, and the spacing between adjacent pillars in the columnar structure is less than 100 nanometers. Figure 3 The length of the columnar structure shown in (d) is about 1 μm, and the aspect ratio is about 10.

[0077] Figure 5 (b) shows the measurement results of the obtained porous body based on the X-ray diffraction (XRD) method. Figure 5 As shown in (b), in the XRD spectrum, although there is a slight peak on the wide-angle side, there is no sharp peak and an almost smooth shape is formed, which confirms that the obtained porous body is almost amorphous. Based on the above results, it can be said that Figure 3 The material shown is porous amorphous silicon.

[0078] Example 3

[0079] Next, silicon (in block form, with a purity of 99.9% or more), aluminum and titanium are mixed in a ratio of Si:Al:Ti=19.5:79.5:1.0 (atomic %), and arc-melted in a vacuum furnace under argon substitution to form a melt at 1400°C. Using the gas atomization device shown in Patent Document 2, the melt is crushed using 10MPa helium to produce Al-Si-Ti alloy powder with a particle size of about 10μm or less. The Al-Si-Ti alloy powder is a eutectic alloy composed of Al, Si and Ti. The Al-Si-Ti alloy powder is immersed in hydrochloric acid at a concentration of 5N and a temperature of 60°C for 24 hours to dissolve Al and Ti, thereby producing a porous body composed of silicon.

[0080] Figure 4 The scanning electron microscope (SEM) image of the obtained porous body is shown. Figure 4 As shown, it was confirmed that the obtained substance formed a porous lamellar structure with an average particle diameter and an average column diameter of about 80 to 100 nm or less. It was also confirmed that the interval between adjacent lamellar layers in the lamellar structure was 50 nm or less.

[0081] Figure 5 (c) in FIG. 1 shows the measurement results of the obtained porous body based on the X-ray diffraction (XRD) method. Figure 5 As shown in (c) in the figure, there is no sharp peak in the XRD spectrum, and a smooth shape is formed, which confirms that the obtained porous body is amorphous rather than crystalline. Based on the above results, it can be said that Figure 4 The material shown is porous amorphous silicon.

[0082] Example 4

[0083] Silicon (in bulk form, with a purity of 99.9% or more) and aluminum are mixed in various proportions to produce a eutectic alloy, and Al is dissolved to produce a porous body composed of silicon. The mixing ratio of Si and Al is set to four types: [Si:Al] = [3:97], [12.5:87.5], [30:70], and [40:60] (atomic %). In addition, a eutectic alloy is produced by a gas atomization method using He gas at a ratio of [Si:Al] = [3:97], and a eutectic alloy is produced by a gas atomization method using Ar gas at a ratio of [Si:Al] = [12.5:87.5]. In addition, a eutectic alloy is produced by a single-roll liquid quenching method at three ratios of [Si:Al] = [12.5:87.5], [30:70], and [40:60].

[0084] In the gas atomization method, in the same manner as in Example 2, first, arc melting is performed on Si and Al mixed in a specified ratio in a vacuum furnace under a state of substitution with argon gas, and the melt is crushed using a gas atomization device shown in Patent Document 2 using 10MPa He gas or Ar gas to produce a eutectic alloy consisting of Al-Si alloy powder with a particle size of about 10μm or less. In the single-roll liquid rapid cooling method, in the same manner as in Example 1, first, arc melting is performed on Si and Al mixed in a specified ratio in a vacuum furnace under a state of substitution with argon gas, and a single-roll casting machine is used to produce a eutectic alloy consisting of a strip-shaped Al-Si alloy with a plate thickness of about 15μm from the melt. The eutectic alloy produced by the above methods is immersed in hydrochloric acid at a concentration of 5N and a temperature of 60°C for 24 hours to dissolve Al, thereby producing a porous body composed of silicon.

[0085] Figure 6 to Figure 10 The scanning electron microscope (SEM) images of the obtained porous bodies are shown respectively. Figure 6 It was confirmed that the porous body obtained by the gas atomization method using He gas with a blending ratio of [Si:Al] = [3:97] formed a columnar structure with an average column diameter of about 100 nm (reference Figure 6 (d) in the figure.

[0086] like Figure 7 As shown, it was confirmed that a porous lamellar structure with an average particle size and an average column diameter of about 100 nm was formed in the porous body obtained by using the gas atomization method using Ar gas at a blending ratio of [Si:Al] = [12.5:87.5] (reference Figure 7 (c) in the figure). It was also confirmed that the interval between adjacent sheets in the sheet structure is about several hundred nanometers. Figure 8 As shown, it was confirmed that a columnar structure with an average column diameter of about 100 nm or less was formed in the porous body obtained by the single roll liquid quenching method at the same blending ratio of [Si:Al]=[12.5:87.5] (reference Figure 8 (b) in the figure. Fig.11 The measurement results of the porous body based on the X-ray diffraction (XRD) method are shown. Fig.11 As shown in FIG. 1 , there is no sharp peak derived from the crystalline substance in the XRD spectrum, and a smooth shape is formed, which confirms that the obtained porous body is amorphous rather than crystalline. Based on this result, it can be said that Figure 8 The material shown is porous amorphous silicon.

[0087] like Fig. 9As shown, it was confirmed that a porous lamellar structure with an average particle size and an average column diameter of about tens of nanometers was formed in the porous body obtained by the single-roll liquid quenching method at a blending ratio of [Si:Al] = [30:70] (reference Fig. 9 (b) in the figure). It was also confirmed that the interval between adjacent sheets in the sheet structure was less than several tens of nanometers.

[0088] like Fig.10 As shown, it was confirmed that a porous sheet structure with an average particle size and an average column diameter of about 100 nm or less was formed in the porous body obtained by the single roll liquid quenching method at a blending ratio of [Si:Al] = [40:60] (reference Fig.10 (b) in the figure). It was also confirmed that the interval between adjacent sheets in the sheet structure was less than several tens of nanometers.

[0089] Example 5

[0090] Manufacturing used Figure 1 and Figure 2 The porous amorphous silicon shown in the figure is used as the negative electrode material of the lithium-ion battery, and the cycle characteristics evaluation test of the battery is carried out. First, the porous amorphous silicon particles, carbon black conductive additive and polyimide binder are dispersed in N-methyl-2-pyrrolidone to prepare a uniform slurry. The slurry is about 1 to 2 mg / cm 2 It was evenly coated on a rolled copper foil in a vacuum, and then heated to 450°C in a vacuum to dry and solidify it. It was used as the negative electrode, pure lithium was used as the counter electrode, and a solution of lithium hexafluorophosphate dissolved in fluoroethylene carbonate at a concentration of 1 mol / L was used as the electrolyte to manufacture a 2032 coin-type half-cell. In addition, as a comparative example, a lithium-ion battery using crystalline Si particles with a diameter of 100 nm as the negative electrode material was also manufactured.

[0091] For each lithium-ion battery manufactured, the porous amorphous silicon electrode was subjected to 100 cycles of charge and discharge based on a current density of 0.5C in the voltage range of 0.005V to 1V, and the crystalline silicon particles were subjected to 100 cycles of charge and discharge based on a current density of 0.25C (1C is 3579mA / g), and the lithium desorption capacity (Capacity) of each cycle was measured. Fig.12 The results of this measurement are shown in FIG. Fig.12As shown, it was confirmed that the maximum capacity of the battery using porous amorphous silicon was about 2000mAh / g Si, and the capacity after 100 cycles was 1600-1700mAh / g Si. Even after 100 cycles, the reduction in capacity was suppressed to about 15-20%. In contrast, it was confirmed that the maximum capacity of the battery using the crystalline Si particles of the comparative example was initially about 2350mAh / g Si, but after 80 cycles, it was reduced to less than 500mAh / g Si. Therefore, it can be said that the lithium-ion battery using porous amorphous silicon as the negative electrode material has good cycle characteristics and high battery capacity.

Claims

1. A porous amorphous silicon, characterized in that: The invention has a lamellar structure with an average particle size of 1nm to 100nm, a double continuous structure in which the lamellar structure is continuous, and a three-dimensional network structure with continuous amorphous silicon and continuous gaps.

2. The porous amorphous silicon according to claim 1, characterized in that: It has a lamellar structure in which the interval between adjacent lamellar layers is 1 nm to 100 nm.

3. The porous amorphous silicon according to claim 1, characterized in that: The average porosity is 10% to 99%.

4. The porous amorphous silicon according to claim 1, characterized in that: The average particle size is 1 nm to 50 nm.

5. A method for manufacturing porous amorphous silicon according to any one of claims 1 to 4, characterized in that: By 10 6 A molten metal and silicon are cooled at a cooling rate of 0.1 K / s or more to form a eutectic alloy composed of the metal and the silicon, and the metal is selectively dissolved from the eutectic alloy by using an acid or an alkali, thereby obtaining porous amorphous silicon. The eutectic alloy is a binary or multi-component eutectic alloy represented by M1-Si, or a ternary or multi-component eutectic alloy represented by M2-Al-Si, wherein M1 is one or more elements selected from Al, Ag, As, Au, Be, Ca, Cr, Cu, Mg, Pd, Pt, Y, Co, Fe, Mn, Ti and Zr, and M2 is one or more elements selected from Ge, P, Na, Sb, Sn, Sc and Sr.

6. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: The eutectic alloy is manufactured by a single-roll liquid quenching method or a double-roll liquid quenching method and is in a strip or foil shape with an average thickness of 0.1 μm to 1 mm.

7. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: The eutectic alloy is produced by a gas atomization method or a water atomization method and is in a powder form with an average particle size of 10 nm to 30 μm.

8. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: The domain size of the silicon phase in the structure of the eutectic alloy is 1 nm to 100 nm.

9. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: The domain size of the metal phase in the structure of the eutectic alloy is 1 nm to 100 nm.

10. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: The domain size of the silicon phase in the structure of the eutectic alloy is 1 nm to 50 nm.

11. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: In terms of atomic percentage, the Si content is 1% to 50%.

12. The method for manufacturing porous amorphous silicon according to claim 5, characterized in that: In terms of atomic percentage, the Si content is 50% to 90%.

13. A secondary battery, characterized in that: The negative electrode material is composed of the porous amorphous silicon according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Manufacturing device of metal powder and manufacturing method of the same

    JP2019014917A

  • Nagative active material for recharge lithium battery, its manufacturing method and recharge lithium battery

    CN1518144A